Amygdala hyperconnectivity in the paranoid state: A transdiagnostic study. (June 2021) - Fan, Linlin; Klein, Hans; Bass, Emily; Springfield, Cassi; Pinkham, Amy
Abstract: Background: Paranoia significantly contributes to social impairments across clinical diagnoses, and amygdala dysfunction has been identified as a neurobiological marker of paranoia among individuals with schizophrenia. Therefore, we aimed to investigate amygdala functional connectivity (FC) in paranoia across diagnoses. Methods: Forty-five patients with recent history of clinically significant paranoid ideation and a current DSM-5 diagnosis of any disorder underwent resting-state functional magnetic resonance imaging either in a paranoid (N = 23) or non-paranoid (N = 22) state. Amygdala FC were compared between paranoid and non-paranoid patients. Supplemental correlation analyses between amygdala FC and paranoia score were performed separately in patients and a non-equivalent healthy control (HC; N = 60) group. Results: Increased FC was found between right amygdala and the prefrontal cortex (PFC) [bilateral medial superior frontal gyrus, anterior cingulate, medial frontal gyrus, the triangular part and the opercular part of the inferior frontal gyrus (IFG); right orbital part of IFG], the frontal cortex (bilateral median cingulate, left precentral gyrus), and subcortical areas (right insula) in the paranoid group compared with the non-paranoid group. No significant between-group differences were observed in left amygdala FC. FC between right amygdala and PFC and frontal cortex was positively correlated with paranoia in patient and HC groups. Conclusion: Paranoia is associated with right amygdala hyperconnectivity with PFC, frontal cortex, and insula. This hyperconnectivity was evident regardless of diagnosis and therefore identify a likely transdiagnostic neural mechanism, which may help to identify treatment targets that could potentially improve the social functioning of individuals with clinical diagnoses. Highlights: Amygdala functional connectivity (FC) was compared between patients who were in either a paranoid or non-paranoid state. Correlations between amygdala FC and levels of paranoia were performed in patient and healthy control (HC) groups. Paranoid patients showed increased right amygdala FC with prefrontal cortex (PFC), frontal cortex, and insula. FC between right amygdala and PFC and frontal cortex was positively correlated with paranoia in patient and HC groups. Our findings suggest a likely transdiagnostic neural mechanism underlying paranoia.